(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate effect of blood pressure stabilization between 6% Hydroxyethyl starch 130/0.4 with Natriclorua 0.9% IV before epidural anesthesia in C-section. Methodology: This is a single blind, randomized control trial among singleton pregnant women in Department of Surgery and Anesthesia, National hospital of Obtetrics and Gynecology from May 2020 to November 2020. Results: Mean period of pre-anesthesia T10 in group 1 was 2,88 ± 0,43 vs 2,85 ± 0,70 in group 2 (p>0,05). Mean period of pre-anesthesia T10 in group 1 was 4,04 ± 0,57 vs 3,80 ± 0,72 in group 2 (p>0,05). The rate of insensitivity in both group was 100%. Value of systolic, diastolic and mean of blood pressure was elevated compare to those before infusion (p<0,01). Min of systolic blood pressure in group 1 was lower than that of group 2 (p<0,05), group 1 systolic BP remained higher than that of group 2. Total amount of infusion in group 2 was significantly higher than that of group 1 (p<0,01). Conclusion: 6% HES 130/0.4 intravenous before epidural anesthesia was an effective method to prevent hypotension. Therefore, this method should be used largely especially in C-section.